Using the Chained Pictures Media in Teaching Writing Skill for English Foreign Language Learners in Islamic Higher Education - Sari Famularsih; Alfin Rosyidha (Universitas Negeri Semarang, 2021)
The research aims to know the implementation of chained pictures as a media to develop EFL learners writing mastery in narative text. To an extent, it intends to find out the result of its implementation toward EFL learners writing skill. The researcher conducted the research using Classroom Action Research (CAR) involving 36 learners; 13 learners of UIN Salatiga and 23 learners UIN Samarinda. CAR incorporated qualitative as well as quantitative data. To get both of the data, the writer uses three techniques of data collection; those are observation, interview and testing. The research is done in three phases; the preliminary research, the cycle 1, and the cycle 2. In the preliminary research, the mean score of the EFL learners is 51.92 out of 100 or 15.4% of the learners passing the minimum standard score. Later, the EFL learners achieved the mean score of 63.92 out of 100 or 43.5% of the learners passing the minimum standard score in the cycle 1. In the cycle 2, the result showed that the mean score is 72.25 out of 100 or 82.5%of the learners passing the minimum standard score. Regarding the observation and questionnaire, it depicts the positive result of the chained picture implementation. The research proved that chained pictures are able to improve EFL learners writing skill on narrative text.